2020
DOI: 10.1007/s11239-020-02174-9
|View full text |Cite
|
Sign up to set email alerts
|

Prominent coagulation disorder is closely related to inflammatory response and could be as a prognostic indicator for ICU patients with COVID-19

Abstract: The new outbreak of Coronavirus Disease 2019 (COVID-19) has emerged as a serious global public health concern. A more in-depth study of blood coagulation abnormality is needed. We retrospectively analyzed 147 consecutive patients with COVID-19 who were admitted to three ICUs in Wuhan from February 9th, 2020 to March 20th, 2020. The baseline coagulation and other characteristics were studied. Our results showed that the prolonged PT, FDP, DD were positively correlated with the levels of neutrophils, ferritin, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
53
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 20 publications
3
53
2
2
Order By: Relevance
“…Compared with moderate patients, severe patients more frequently had dyspnea and lymphopenia, with markedly higher levels of IL-2R, IL-6, IL-10, and TNF-α [8]. The severe inflammatory state secondary to COVID-19 leads to severe derangement of hemostasis and prominent alternation of coagulation parameters [4,[9][10][11]. It is generally believed that deterioration of coagulation parameters during the disease course is closely associated with COVID-19 worsening and death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with moderate patients, severe patients more frequently had dyspnea and lymphopenia, with markedly higher levels of IL-2R, IL-6, IL-10, and TNF-α [8]. The severe inflammatory state secondary to COVID-19 leads to severe derangement of hemostasis and prominent alternation of coagulation parameters [4,[9][10][11]. It is generally believed that deterioration of coagulation parameters during the disease course is closely associated with COVID-19 worsening and death.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with the fact that PT-act < 75% is an independent risk factor for patient death, we argue that PT-act is a useful index for predicting COVID-19 patient death. Liu et al [11] reported that using ROC analyses, the AUC values for PT, FDP, and D-dimer at admission were 0.892, 0.81, and 0.809, respectively, for predicting inhospital mortality in patients with COVID-19. Another study on COVID-19 also indicated that the AUCs of PT and Ddimer at admission were 0.643 and 0.742 for predicting mortality, and they increased to 0.937 and 0.851, respectively, at the composite endpoint [22].…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value and biomarkers of the SARS-CoV-2 and its effects on the CNS and PNS vary among subjects depending on age, comorbidities, immunocompetency, and disease severity. As SARS-CoV-2 exerts its mechanism via overactivation of the inflammatory response, increased hypercoagulability, and decreased anticoagulable processes, inflammatory markers, and coagulation tests may be predictive of prognosis [47]. A study conducted by Liu et al [47] reported conventional hematologic analysis examining coagulation parameters; Prothrombin time, fibrin degradation products (FDP), and D-dimer (DD) served as prognostic biomarkers for individuals with increased mortality in COVID-19 confirmed ICU subjects.…”
Section: Discussionmentioning
confidence: 99%
“…As SARS-CoV-2 exerts its mechanism via overactivation of the inflammatory response, increased hypercoagulability, and decreased anticoagulable processes, inflammatory markers, and coagulation tests may be predictive of prognosis [47]. A study conducted by Liu et al [47] reported conventional hematologic analysis examining coagulation parameters; Prothrombin time, fibrin degradation products (FDP), and D-dimer (DD) served as prognostic biomarkers for individuals with increased mortality in COVID-19 confirmed ICU subjects. The study also reported antithrombin III (ATIII) as a biomarker for increased survival in ICU patients, concluding PT, DD, FDP, and ATIII to be predictors of prognosis [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation